Meta-fluidic-surfaces for electromagnetic wave manipulations - Yan, Libin (2019)
Metasurfaces are subwavelength-thick planar materials artificially designed with distinctive electromagnetic properties. The flexibility of tailoring both the permittivity and permeability of the metasurface enables its extraordinary electromagnetic response that cannot be found in natural materials. The extraordinary electromagnetic properties of metasurfaces lead to many promising and practical applications. This doctorate thesis focuses on the design, simulation, fabrication and experimental measurement of meta-fluidic-surface for tailoring the optical properties of electromagnetic waves. Specifically, three types of meta-fluidic-surface is studied and discussed, namely: (1) dispersion-controllable metasurface for tailoring the dispersion property of metasurface; (2) polarization-independent tunable metasurface for polarization-independent beam control, and (3) Tunable birefringent metasurface for the manipulation of birefringence.